'Too Many Empty Homes, Too Many Homeless' – A Novel Design and Procurement Framework for Transforming Empty Homes through Sustainable Solutions. (March 2017) - Ceranic, Boris; Markwell, Graham; Dean, Angela
Abstract: The Retro-Tek research project investigates the potential of existing buildings in the UK contributing towards the EU 2050 CO2 target, through a sustainable retrofit programme aimed specifically at empty homes. It proposes a novel design and procurement methodology to bring empty homes back into use, integrate sustainable technologies and materials and offer them back to the market. Along with the obvious environmental sustainability benefits, it also assists communities and areas in need of regeneration, supporting the developments to both help address housing shortages and tackle socio-economic problems with empty, dilapidated dwellings. The project has formed a consortium of stakeholders and established unique design and procurement processes and methodologies relevant to the sustainable retrofit process. Their viability was tested via undertaking two case studies of representative empty homes, establishing results within a measurable data format. The research further developed a commercial output model based on financing, procurement, the supply chain and the project management process and is currently applying for funding to launch a major scheme of bringing 1000 empty homes back in use by 2020.